LOGICO-SEMANTIC RELATIONS IN BATAK TOBA WEDDING CEREMONY - TRIANA MANALU; MEISURI MEISURI; WIDYA ANDAYANI (State University of Medan, 2021)
The research focused on logico-semantic relations in the Batak Toba wedding ceremony. The research aimed to discover the types of logico-semantic relations used in mangulosi and describe how they were realized in the Batak Toba wedding ceremony. The research was conducted by using the descriptive qualitative method. The data were taken from 2 wedding ceremony videos from 104 clause complexes selected. The study's finding showed that there were 9 of the logico-semantic relations types used in the Batak Toba wedding ceremony. They were consecutively hypotactic enhancement, hypotactic elaboration, paratactic enhancement, paratactic elaboration, hypotactic locution, paratactic extension, hypotactic extension, hypotactic idea, and paratactic idea. The logico-semantic relations were realized in mangulosi in Batak Toba wedding ceremony consecutively conjunction, verb, preposition, prepositional phrase, and adverbial clause which the utterances aimed about the message, prediction in the future, advice, hope, and blessing of hulahula for the bridegroom.